Armed Conflicts and Household Socioeconomic Status in the Lake Chad Basin: A Random Coefficient Model Approach - Olarinde M.O.; Osabohien R.; Osabuohien E. (Walter de Gruyter GmbH, 2025)
This study extends the existing literature on the relationship between armed conflicts and the socioeconomic status of households in Lake Chad Basin (LCB) countries by adopting a random coefficient model to analyse micro-panel data covering the 1997?2020 periods. The random coefficient approach allows for country-specific effects in explaining variations in both the nature and degree of the effects of conflict due to differing country characteristics. The result evidenced a significant negative effect of the average impact of armed conflict on poverty, while the coefficient of educational outcome is insignificant. The country-specific results point to significant inter-country variations in the impact of armed conflicts on poverty and education outcomes. The descriptive statistics result shows that the inter-country variations could be attributed to differing quality of institutions. Finally, environmental degradation and macroeconomic uncertainties do not appear to bear a systematic relationship with households? level of socioeconomic status in the Lake Chad Basin. These findings indicate that a uniform and blanket adoption of public policies by government in Lake Chad Basin countries will not yield a significant positive result. Therefore, governments, practitioners and academicians should contextualise policies/recommendations meant to improve socioeconomic status of households in conflict, while strengthening the quality of institutions to ameliorate the impact of conflict on socioeconomic status (SES) of households. ? 2024 Walter de Gruyter GmbH. All rights reserved.